A composite modified lithium-rich manganese-based positive electrode material and preparation method thereof and lithium-ion battery
By introducing M and T metal ions on the precursor surface of the lithium-rich manganese-based positive electrode material and forming a surface in-situ composite structure with high temperature sintering, the problems of material cycle stability and rate performance are solved, and significant performance improvement is achieved.
Patent Information
- Application Number
- CN202410052577.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-01-12
AI Technical Summary
The lithium-rich manganese-based positive electrode material has problems such as rapid capacity and voltage attenuation and gas generation during the circulation process. The prior art is difficult to effectively suppress the cracking of secondary particles and the dissolution of Mn ions, which affects its application.
M metal ions and T metal ions are introduced on the surface of the precursor of lithium-rich materials, and a surface in-situ composite modified structure is formed through high-temperature sintering. The T ions are mainly segregated on the surface and grain boundaries of primary particles, and the M ion gradient is distributed in primary particles. In the lattice, a LifTgO2 cladding layer and a Li1+eMnaNibMcTdO2 core are formed.
It significantly improves the cyclic stability and rate performance of the material, inhibits secondary particle cracking and Mn ion dissolution, and improves the electrochemical performance of the material.
Smart Images

Figure CN117894947B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery materials, and in particular to a composite modified lithium-rich manganese-based positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-rich manganese-based layered oxide cathodes with high capacity and low cost are very promising for large-scale application in the next generation of high-energy-density lithium-ion batteries. However, this material has problems such as rapid capacity and voltage decay during cycling and the accompanying gas generation, which affect its practical application. For commonly used polycrystalline lithium-rich materials (spherical secondary particles formed by the agglomeration of smaller primary particles), the above problems during the cycling process are mainly caused by the following reasons: (1) During cycling, the lattice oxygen of the material gradually precipitates from the surface of the primary particles, and Mn ions also dissolve in large quantities from the surface of the primary particles, which causes some transition metal ions in the material to lose their electrochemical activity; (2) During cycling, the secondary particles of the material gradually crack, which not only aggravates the side reactions such as oxygen precipitation and Mn dissolution, but also causes the electrical contact inside the secondary particles to deteriorate.
[0003] Using electrochemically inert elements (such as Al 3+ , Ti 4+ , Zr 4+) Surface doping of materials can effectively improve the stability of the surface structure of the materials, so it is a common means to improve the cycle performance of lithium-rich materials. However, the above method often causes a significant decrease in the initial capacity and rate performance of the material, and cannot inhibit the cracking of secondary particles during cycling. The literature (Energy Environ. Sci., 2021, 14, 6616–6626) has reported a modification strategy that uses high-valent (5-valent, 6-valent) transition metal ions to reduce the primary particle size of high-nickel materials and change the stacking mode of primary particles. This method can significantly inhibit the cracking of secondary particles of high-nickel materials during cycling, thereby significantly improving the cycle performance. However, for lithium-rich materials, the reduction in the particle size of primary particles will lead to more serious oxygen precipitation and Mn dissolution problems, which is not conducive to cycle performance. Chinese patent CN110383542B once disclosed a doped lithium-rich material with a surface covered with tungsten compounds / lithium tungsten compounds. The protective effect of tungsten compounds / lithium tungsten compounds can improve the electrochemical properties of the material. However, the tungsten-containing compound in this patent is introduced on the surface of the finished material rather than the precursor surface. Since the particle size and stacking mode of the primary particles of the material cannot be further regulated in this process, the capacity decay and gas production problems caused by the cracking of the secondary particles during the cycle of the material cannot be effectively improved. Chinese patent CN113078316A discloses a lithium molybdate-coated lithium-rich manganese-based positive electrode material and a preparation method thereof, but the capacity decay and gas production problems caused by the cracking of the secondary particles during the cycle of the material prepared by this method are also not effectively suppressed.
[0004] Therefore, how to more effectively improve the cyclic stability of lithium-rich materials is an urgent problem that needs to be solved to promote the practical application of lithium-rich materials. Summary of the invention
[0005] The present invention simultaneously introduces M metal ions that are easy to enter the layered structure of the lithium-rich material during sintering, and T metal ions that are not easy to enter the layered structure of the lithium-rich material during sintering and can regulate the morphology and stacking mode of the primary particles of the lithium-rich material on the surface of the precursor of the lithium-rich material. Subsequently, a lithium-rich manganese-based positive electrode material with surface in-situ composite modification is obtained by high-temperature sintering. After high-temperature sintering, the oxide of T is mainly segregated on the surface of the primary particles and the grain boundaries, and a small amount diffuses into the surface lattice of the material; after high-temperature sintering, the M ions enter the primary particle lattice and are distributed in a gradient (the content gradually decreases from the outside to the inside). The cycle stability of the lithium-rich material with such structural characteristics can be significantly improved, and the rate performance can also be improved to a certain extent.
[0006] One of the purposes of the present invention is to provide a composite modified lithium-rich manganese-based positive electrode material.
[0007] A second object of the present invention is to provide a method for preparing a composite modified lithium-rich manganese-based positive electrode material.
[0008] The third object of the present invention is to provide a lithium-ion battery comprising the composite modified lithium-rich manganese-based positive electrode material.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides a composite modified lithium-rich manganese-based positive electrode material, wherein the composite modified lithium-rich manganese-based positive electrode material is composed of: xLi 1+e Mn a Ni b M c T d O2@(1-x)Li f T g O2,
[0011] Among them, 0.95≤x≤0.995; 0.5<a≤0.9, 0<b≤0.5, 0<c≤0.2, 0<d≤0.01, 0<e≤0.2, 0<f≤1, 0.1≤g≤1;
[0012] M is one or more selected from Ti, Zr, Sn, Mg, Ca, Al and La; T is one or more selected from W, Mo, Ta and Nb;
[0013] The morphology structure of the composite modified lithium-rich manganese-based positive electrode material is a spherical secondary particle formed by agglomeration of primary particles, and the structure of the primary particles includes: 1+e Mn a Ni b M c T d The core of O2 and Li f T g The coating layer of O2, in which the T metal ions in the inner core exist in the surface lattice of the inner core, and the M metal ions exist in the lattice of the inner core and the content gradually decreases from the outside to the inside.
[0014] The following is a detailed description:
[0015] The composition of the composite modified lithium-rich manganese-based positive electrode material of the present invention is: xLi 1+e Mn a Ni b M c T d O2@(1-x)Li f T gO2, wherein 0.95≤x≤0.995; 0.5<a≤0.9, 0<b≤0.5, 0<c≤0.2, 0<d≤0.01, 0<e≤0.2, 0<f≤1, 0.1≤g≤1; M is one or more selected from Ti, Zr, Sn, Mg, Ca, Al and La; T is one or more selected from W, Mo, Ta and Nb;
[0016] For example, the composition of the composite modified lithium-rich manganese-based positive electrode material is, for example, 0.98Li 1.19 Mn 0.575 Ni 0.2 Ti 0.02 W 0.005 O2@0.02Li2WO4, but not limited thereto.
[0017] The material has the following structural characteristics:
[0018] (1) The morphology is spherical secondary particles formed by the agglomeration of smaller primary particles;
[0019] Preferably, the primary particles are plate-like crystals, and the sizes in three mutually perpendicular directions are respectively in the range of 20-500 nm, 20-500 nm, and 10-200 nm, and the particle size of the spherical secondary particles is in the range of 1-20 μm.
[0020] (2) Primary particle structure Figure 1 As shown, including: Li 1+e Mn a Ni b M c T d The core of O2 and Li f T g The present invention introduces T metal ions and M metal ions simultaneously on the surface of the lithium-rich manganese-based positive electrode material precursor: after high-temperature sintering, the T ions are mainly segregated on the primary particle surface and grain boundaries to form Li f T g O2 coating layer, and a small amount diffuses into the surface lattice of the inner core; M ions enter the inner core lattice after high-temperature sintering and are distributed in a gradient (the content gradually decreases from the outside to the inside).
[0021] In a second aspect, the present invention provides a method for preparing a composite modified lithium-rich manganese-based positive electrode material, comprising the following steps:
[0022] (1) According to the composite modified lithium-rich manganese-based oxide positive electrode material xLi 1+e Mn a Ni b M c T d O2@(1-x)Lif T g The stoichiometric ratio of each element in the O2 composition (i.e., the stoichiometric ratio of each element in the core and the shell) is as follows: Weigh the Li compound, the Mn compound, the Ni compound, the M compound, and the T compound;
[0023] (2) dissolving a Ni compound and a Mn compound in water to obtain a liquid mixture; then adding an aqueous solution of a soluble alkali or an aqueous solution of a soluble carbonate to the liquid mixture under stirring, filtering, washing, and drying the obtained precipitate to obtain a lithium-rich manganese-based positive electrode material precursor;
[0024] (3) introducing the compound M and the compound T into the surface of the lithium-rich manganese-based positive electrode material precursor obtained in step (2) by a liquid phase method or a solid phase method to obtain a composite modified lithium-rich manganese-based positive electrode material precursor;
[0025] (4) The composite modified lithium-rich manganese-based positive electrode material precursor obtained in step (3) is evenly mixed with a Li compound, and pre-fired and calcined in a mixed atmosphere of an inert gas and oxygen, and cooled to obtain a composite modified lithium-rich manganese-based positive electrode material.
[0026] The following is a detailed description of each step:
[0027] Step (1):
[0028] According to xLi 1+e Mn a Ni b M c T d O2@(1-x)Li f T g The stoichiometric ratio of each element in the O2 composition is as follows: Li compound, Mn compound, Ni compound, M compound and T compound are weighed.
[0029] The Li compound is one or more selected from lithium carbonate, lithium oxide, lithium hydroxide, and lithium nitrate;
[0030] The Mn compound is one or more selected from the group consisting of Mn oxide, Mn hydroxide, Mn carbonate, Mn nitrate, Mn chloride, and Mn sulfate;
[0031] The Ni compound is one or more selected from Ni oxide, Ni hydroxide, Ni carbonate, Ni nitrate, Ni chloride, and Ni sulfate;
[0032] The compound of M is one or more selected from the group consisting of oxides of M, hydroxides of M, carbonates of M, nitrates of M, chlorides of M, and sulfates of M;
[0033] The compound of T is one or more selected from the group consisting of oxides of T, hydroxides of T, carbonates of T, nitrates of T, chlorides of T, sulfates of T, and oxygen-containing acid salts corresponding to T.
[0034] Step (2):
[0035] An aqueous solution of a soluble alkali or an aqueous solution of a soluble carbonate is added in excess to completely precipitate Ni ions and Mn ions.
[0036] Step (3):
[0037] Step (3) includes the following situations:
[0038] A. When the compound M and the compound T are both soluble in water, a liquid phase method can be used, and the liquid phase method includes the following two methods:
[0039] (a) Evaporation to dryness: The lithium-rich manganese-based cathode material precursor obtained in step (2) is dispersed in water, and then the compound M and the compound T are dissolved in water, and the aqueous solution of the compound M and the aqueous solution of the compound T are respectively dropped therein under stirring to obtain a liquid mixture; finally, the liquid mixture is evaporated to dryness under continuous heating and stirring to obtain a composite modified lithium-rich manganese-based cathode material precursor.
[0040] (b) Precipitation method: The lithium-rich manganese-based positive electrode material precursor obtained in step (2) is dispersed in water, and then the compound M and the compound T are dissolved in water, and the aqueous solution of the compound M and the aqueous solution of the compound T are respectively dropped therein under stirring to obtain a liquid mixture; finally, an aqueous solution of a soluble alkali or an aqueous solution of a soluble carbonate is added to the liquid mixture under stirring, and the obtained precipitate is filtered, washed, and dried to obtain a composite modified lithium-rich manganese-based positive electrode material precursor.
[0041] B. When the compound of M and the compound of T are insoluble in water, a solid phase method may be used, and the solid phase method comprises the following steps:
[0042] The lithium-rich manganese-based positive electrode material precursor obtained in step (2) is mixed with the compound of M and the compound of T in a high-speed mixer or a ball mill to obtain a composite modified lithium-rich manganese-based positive electrode material precursor.
[0043] Preferably, the speed of the high-speed mixer is 500 to 10,000 r / min, and the mixing time is 1 to 72 h;
[0044] Preferably, the rotation speed of the ball mill is 200 to 800 r / min, the ball milling time is 1 to 72 h, and the ball-to-material weight ratio is 5 to 50:1.
[0045] Step (4):
[0046] Preferably, the volume ratio of the inert gas to oxygen is 1:(0.001-100), and the inert gas is one or more of nitrogen and argon.
[0047] Preferably, the pre-burning temperature is 200-700°C, and the pre-burning time is 0.5-10h;
[0048] Preferably, the calcination temperature is 500-1000° C., and the calcination time is 2-25 hours.
[0049] The composition of the composite modified lithium-rich manganese-based positive electrode material obtained by the method of the second aspect is: 1+ e Mn a Ni b M c T d O2@(1-x)Li f T g O2, wherein 0.95≤x≤0.995; 0.5<a≤0.9, 0<b≤0.5, 0<c≤0.2, 0<d≤0.01, 0<e≤0.2, 0<f≤1, 0.1≤g≤1; M is one or more selected from Ti, Zr, Sn, Mg, Ca, Al and La; T is one or more selected from W, Mo, Ta and Nb; the morphology structure of the composite modified lithium-rich manganese-based positive electrode material is a spherical secondary particle formed by agglomeration of primary particles, and the structure of the primary particles includes: a composition of Li 1+ e Mn a Ni b M c T d The core of O2 and Li f T g The coating layer of O2, in which the T metal ions in the inner core exist in the surface lattice of the inner core, and the M metal ions exist in the lattice of the inner core and the content gradually decreases from the outside to the inside.
[0050] In a third aspect, the present invention further provides a lithium-ion battery comprising the above-mentioned positive electrode material.
[0051] Beneficial Effects
[0052] (1) The T oxide segregated on the surface of the primary particles during the sintering process can regulate the morphology and stacking mode of the primary particles of the material, inhibit the cracking of the secondary particles during the cycle, and can also uniformly coat the primary particles of the material. The above effects help improve the cycle performance of the material. In addition, reducing the size of the primary particles also helps improve the rate performance of the material.
[0053] (2) During high-temperature sintering, a small amount of T ions diffused into the surface lattice help improve the stability of the material's surface structure.
[0054] (3) A large number of M ions entering the material lattice can further enhance the structural stability of the surface and bulk of the primary particles, thereby improving the cycle performance degradation and gas production problems caused by the reduction in primary particle size.
[0055] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The primary particle structure and element distribution schematic diagram of the composite modified lithium-rich manganese-based positive electrode material of the present invention are shown. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0058] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0059] Comparative Example 1 Lithium-rich manganese-based oxide material Li 1.2 Mn 0.6 Ni 0.2 O2
[0060] The preparation steps are as follows:
[0061] Li2CO3, MnSO4, and NiSO4 are weighed according to the stoichiometric ratio of each element. NiSO4 and MnSO4 are first dissolved in water to obtain a liquid mixture, and then an excess of sodium carbonate aqueous solution is added to the liquid mixture under stirring (the amount of sodium carbonate must exceed the sum of the amounts of NiSO4 and MnSO4), and the obtained carbonate precipitate is filtered, washed, and dried to obtain a lithium-rich manganese-based positive electrode material precursor.
[0062] The above precursors were mixed evenly with the weighed Li2CO3, and pre-sintered at 500°C for 5 h and calcined at 900°C for 15 h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.6 Ni 0.2 O2.
[0063] Comparative Example 2Li 1.2 Mn0.58 Ni 0.2 Ti 0.02 O2
[0064] The preparation steps are as follows:
[0065] Li2CO3, MnSO4, NiSO4 and TiO2 were weighed according to the stoichiometric ratio of each element. First, a lithium-rich manganese-based positive electrode material precursor was prepared according to the process in Comparative Example 1.
[0066] Subsequently, the weighed TiO2 (particle size 20nm) was mixed with the above precursor at a speed of 2000r / min for 2h using a high-speed mixer, and then mixed evenly with the weighed Li2CO3. Finally, the mixture was pre-sintered at 500℃ for 5h and calcined at 900℃ for 15h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the modified lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.58 Ni 0.2 Ti 0.02 O2.
[0067] Comparative Example 3 0.98Li 1.19 Mn 0.595 Ni 0.2 W 0.005 O2@0.02Li2WO4
[0068] Li2CO3, MnSO4, NiSO4 and Li2WO4 were weighed according to the stoichiometric ratio of each element. First, a lithium-rich manganese-based positive electrode material precursor was prepared according to the process in Comparative Example 1.
[0069] Subsequently, the weighed Li2WO4 was mixed with the above precursor at a speed of 2000r / min for 2h using a high-speed mixer, and then mixed evenly with the weighed Li2CO3. Finally, the mixture was pre-sintered at 500℃ for 5h and calcined at 900℃ for 15h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the modified lithium-rich manganese-based positive electrode material 0.98Li 1.19 Mn 0.595 Ni 0.2 W 0.005 O2@0.02Li2WO4.
[0070] Example 1 0.98Li 1.19 Mn 0.575 Ni 0.2 Ti 0.02 W 0.005 O2@0.02Li2WO4
[0071] Li2CO3, MnSO4, NiSO4, TiO2 and Li2WO4 were weighed according to the stoichiometric ratio of each element. First, a lithium-rich manganese-based positive electrode material precursor was prepared according to the process in Comparative Example 1.
[0072] Subsequently, the weighed TiO2 (particle size 20nm), Li2WO4 and the above precursors were mixed with a high-speed mixer at a speed of 2000r / min for 2h, and then mixed with the weighed Li2CO3. Finally, the mixture was pre-sintered at 500℃ for 5h and calcined at 900℃ for 15h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the lithium-rich manganese-based positive electrode material 0.98Li 1.19 Mn 0.575 Ni 0.2 Ti 0.02 W 0.005 O2@0.02Li2WO4.
[0073] Example 2 0.98Li 1.19 Mn 0.575 Ni 0.2 Zr 0.02 Mo 0.005 O2@0.02Li2MoO4
[0074] Li2CO3, MnSO4, NiSO4, ZrO2 and MoO3 were weighed according to the stoichiometric ratio of each element. First, a lithium-rich manganese-based positive electrode material precursor was prepared according to the process in Comparative Example 1.
[0075] Subsequently, the weighed ZrO2 (particle size 20nm), MoO3 (particle size 20nm) and the above precursors were mixed with a high-speed mixer at a speed of 2000r / min for 2h, and then mixed evenly with the weighed Li2CO3. Finally, the mixture was pre-sintered at 500℃ for 5h and calcined at 900℃ for 15h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the lithium-rich manganese-based positive electrode material 0.98Li 1.19 Mn 0.575 Ni 0.2 Zr 0.02 Mo 0.005 O2@0.02Li2MoO4.
[0076] Example 3 0.98Li 1.19 Mn 0.6 Ni 0.19 Mg 0.01 Nb 0.01 O2@0.02LiNbO3
[0077] Li2CO3, MnSO4, NiSO4, MgO and Nb2O5 were weighed according to the stoichiometric ratio of each element. First, a lithium-rich manganese-based positive electrode material precursor was prepared according to the process in Comparative Example 1.
[0078] Subsequently, the weighed MgO (particle size 20nm), Nb2O5 (particle size 20nm) and the above precursors were mixed with a high-speed mixer at a speed of 2000r / min for 2h, and then mixed with the weighed Li2CO3. Finally, the mixture was pre-sintered at 500℃ for 5h and calcined at 900℃ for 15h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the lithium-rich manganese-based positive electrode material 0.98Li 1.19 Mn 0.6 Ni 0.19 Mg 0.01 Nb 0.01 O2@0.02LiNbO3.
[0079] Example 4 0.99Li 1.2 Mn 0.575 Ni 0.2 Al 0.02 Mo 0.005 O2@0.01Li2MoO4
[0080] Li2CO3, MnSO4, NiSO4, Al2O3 and MoO3 were weighed according to the stoichiometric ratio of each element. First, a lithium-rich manganese-based positive electrode material precursor was prepared according to the process in Comparative Example 1.
[0081] Subsequently, the weighed Al2O3 (particle size 20nm), MoO3 (particle size 20nm) and the above precursors were mixed with a high-speed mixer at a speed of 1500r / min for 3h, and then mixed with the weighed Li2CO3. Finally, the mixture was pre-sintered at 500℃ for 5h and calcined at 900℃ for 15h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the lithium-rich manganese-based positive electrode material 0.99Li 1.2 Mn 0.575 Ni 0.2 Al 0.02 Mo 0.005 O2@0.01Li2MoO4.
[0082] Example 5 0.99Li 1.19 Mn 0.575 Ni 0.2 Sn 0.02 W 0.005 O2@0.01Li2WO4
[0083] Li2CO3, MnSO4, NiSO4, SnO2 and WO3 were weighed according to the stoichiometric ratio of each element. First, a lithium-rich manganese-based positive electrode material precursor was prepared according to the process in Comparative Example 1.
[0084] Subsequently, the weighed SnO2 (particle size 20nm) and WO3 (particle size 20nm) were mixed with the above precursors at a speed of 2500r / min for 1h using a high-speed mixer, and then mixed evenly with the weighed Li2CO3. Finally, the mixture was pre-sintered at 500℃ for 5h and calcined at 900℃ for 15h in a mixed atmosphere of nitrogen and oxygen (volume ratio 1:1) to obtain the lithium-rich manganese-based positive electrode material 0.99Li 1.19 Mn 0.575 Ni 0.2 Sn 0.02 W 0.005 O2@0.01Li2WO4.
[0085] The prepared materials were used as positive electrode materials and graphite was used as negative electrode materials to assemble into batteries. Constant current charge and discharge tests were performed at 25°C. The charge and discharge voltage range was 2 to 4.8V, and a current density of 200mA / g was defined as 1C. The results are shown in Table 1.
[0086] Table 1
[0087]
[0088] Note: The amount of gas generated is obtained by measuring the volume change before and after the battery cycle using the water displacement method.
[0089] The test results in Comparative Examples 1-3 and Example 1 show that:
[0090] (1) Using TiO2 alone to dope the surface of lithium-rich material particles can significantly improve the material's cycle capacity retention rate and gas production, but the initial capacity and rate performance will be significantly reduced.
[0091] (2) Using Li2WO4 alone to modify the morphology of lithium-rich material particles can simultaneously improve the initial capacity and rate of the material. The inhibition of secondary particle cracking improves the cycle capacity retention rate to a certain extent. However, the reduction in particle size is not conducive to a significant improvement in the material's cycle performance and aggravates the gas production problem during the cycle.
[0092] (3) The in-situ composite modification of the surface of lithium-rich materials using TiO2 and Li2WO4 can significantly improve the material's cycle capacity retention rate, and the material's initial capacity, rate performance and gas production problems are also improved to a certain extent, so the overall effect is optimal.
[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A composite modified lithium-rich manganese-based positive electrode material, characterized in that: The composition of the composite modified lithium-rich manganese-based positive electrode material is: xLi 1+e Mn a Ni b M c T d O2@(1-x)Li f T g O2, Among them, 0.95≤x≤0.995; 0.5<a≤0.9, 0<b≤0.5, 0<c≤0.2, 0<d≤0.01, 0<e≤0.2, 0<f≤1, 0.1≤g≤1; M is one or more selected from Ti, Zr, Sn, Mg, Ca, Al and La; T is one or more selected from W, Mo, Ta and Nb; The morphology structure of the composite modified lithium-rich manganese-based positive electrode material is a spherical secondary particle formed by agglomeration of primary particles, and the structure of the primary particles includes: 1+e Mn a Ni b M c T d The core of O2 and Li f T g The coating layer of O2, in which the T metal ions in the core exist in the surface lattice of the core, and the M metal ions exist in the lattice of the core and the content gradually decreases from the outside to the inside; The preparation method of the composite modified lithium-rich manganese-based positive electrode material comprises the following steps: (1) According to the composite modified lithium-rich manganese-based oxide positive electrode material composition xLi 1+e Mn a Ni b M c T d O2@(1-x)Li f T g The stoichiometric ratio of each element in O2 Weigh the compound of Li, the compound of Mn, the compound of Ni, the compound of M and the compound of T; (2) dissolving a Ni compound and a Mn compound in water to obtain a liquid mixture; then adding an aqueous solution of a soluble alkali or an aqueous solution of a soluble carbonate to the liquid mixture under stirring, filtering, washing, and drying the obtained precipitate to obtain a lithium-rich manganese-based positive electrode material precursor; (3) introducing the compound M and the compound T into the surface of the lithium-rich manganese-based positive electrode material precursor obtained in step (2) by a liquid phase method or a solid phase method to obtain a composite modified lithium-rich manganese-based positive electrode material precursor; (4) The composite modified lithium-rich manganese-based positive electrode material precursor obtained in step (3) is evenly mixed with a Li compound, and pre-fired and calcined in a mixed atmosphere of an inert gas and oxygen, and cooled to obtain a composite modified lithium-rich manganese-based positive electrode material.
2. The composite modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The primary particles are plate-like crystals, and the sizes in three mutually perpendicular directions are respectively in the range of 20-500nm, 20-500nm, and 10-200nm, and the particle size of the spherical secondary particles is in the range of 1-20μm.
3. A method for preparing the composite modified lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: The steps include: (1) According to the composite modified lithium-rich manganese-based oxide positive electrode material composition xLi 1+e Mn a Ni b M c T d O2@(1-x)Li f T g The stoichiometric ratio of each element in O2 Weigh the compound of Li, the compound of Mn, the compound of Ni, the compound of M and the compound of T; (2) dissolving a Ni compound and a Mn compound in water to obtain a liquid mixture; then adding an aqueous solution of a soluble alkali or an aqueous solution of a soluble carbonate to the liquid mixture under stirring, filtering, washing, and drying the obtained precipitate to obtain a lithium-rich manganese-based positive electrode material precursor; (3) introducing the compound M and the compound T into the surface of the lithium-rich manganese-based positive electrode material precursor obtained in step (2) by a liquid phase method or a solid phase method to obtain a composite modified lithium-rich manganese-based positive electrode material precursor; (4) The composite modified lithium-rich manganese-based positive electrode material precursor obtained in step (3) is evenly mixed with a Li compound, and pre-fired and calcined in a mixed atmosphere of an inert gas and oxygen, and cooled to obtain a composite modified lithium-rich manganese-based positive electrode material.
4. The preparation method according to claim 3, characterized in that: In step (1), The Li compound is one or more selected from lithium carbonate, lithium oxide, lithium hydroxide, and lithium nitrate; The Mn compound is one or more selected from the group consisting of Mn oxide, Mn hydroxide, Mn carbonate, Mn nitrate, Mn chloride, and Mn sulfate; The Ni compound is one or more selected from Ni oxide, Ni hydroxide, Ni carbonate, Ni nitrate, Ni chloride, and Ni sulfate; The compound of M is one or more selected from the group consisting of oxides of M, hydroxides of M, carbonates of M, nitrates of M, chlorides of M, and sulfates of M; The compound of T is one or more selected from the group consisting of oxides of T, hydroxides of T, carbonates of T, nitrates of T, chlorides of T, sulfates of T, and oxygen-containing acid salts corresponding to T.
5. The preparation method according to claim 3, characterized in that: In step (3), The liquid phase method includes the following two methods: (a) Evaporation to dryness method: The lithium-rich manganese-based cathode material precursor obtained in step (2) is dispersed in water, and then the compound M and the compound T are dissolved in water, and the aqueous solution of the compound M and the aqueous solution of the compound T are respectively dropped therein under stirring to obtain a liquid mixture; finally, the liquid mixture is evaporated to dryness under continuous heating and stirring to obtain a composite modified lithium-rich manganese-based cathode material precursor; (b) Precipitation method: The lithium-rich manganese-based positive electrode material precursor obtained in step (2) is dispersed in water, and then the compound M and the compound T are dissolved in water, and the aqueous solution of the compound M and the aqueous solution of the compound T are respectively dropped therein under stirring to obtain a liquid mixture; finally, an aqueous solution of a soluble alkali or an aqueous solution of a soluble carbonate is added to the liquid mixture under stirring, and the obtained precipitate is filtered, washed, and dried to obtain a composite modified lithium-rich manganese-based positive electrode material precursor.
6. The preparation method according to claim 3, characterized in that: In step (3), The solid phase method comprises the following steps: The lithium-rich manganese-based positive electrode material precursor obtained in step (2) is mixed with the compound of M and the compound of T in a high-speed mixer or a ball mill to obtain a composite modified lithium-rich manganese-based positive electrode material precursor.
7. The preparation method according to claim 6, characterized in that: The speed of the high-speed mixer is 500-10000 r / min, and the mixing time is 1-72 h; The rotation speed of the ball mill is 200-800 r / min, the ball milling time is 1-72 h, and the ball-to-material weight ratio is 5-50:
1.
8. The preparation method according to claim 3, characterized in that: In step (4), The volume ratio of the inert gas to oxygen is 1:(0.001-100), and the inert gas is one or more of nitrogen and argon.
9. The preparation method according to claim 3, characterized in that: In step (4), The pre-burning temperature is 200-700°C and the pre-burning time is 0.5-10h; The calcination temperature is 500-1000° C., and the calcination time is 2-25 hours.
10. A lithium ion battery, characterized in that: The invention relates to a composite modified lithium-rich manganese-based positive electrode material comprising the composite modified lithium-rich manganese-based positive electrode material according to claim 1 or 2 or a composite modified lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 3 to 9.
Citation Information
Patent Citations
Positive electrode active materials containing lithium-rich manganese-based oxides and lithium tungsten compounds or additional tungsten compounds thereon, and positive electrodes for lithium secondary batteries.
CN110383542B
Lithium molybdate coated lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN113078316A
Concentration gradient doped lithium-rich manganese-based positive electrode material and preparation method thereof
CN113213553A
Preparation method of cobalt-free positive electrode material
CN113745494A
High-nickel positive electrode material, preparation method thereof and battery
CN117832449A